Meningkatkan Soft Skills Profil Pelajar Pancasila Melalui Proyek Pembuatan Pameran Karya Seni Rupa Virtual Di Kelas XI MIPA 4 Sekolah Menengah Atas Negeri I Muaro Jambi - Yasmen, Emri (STIT Muhammadiyah Paciran Lamongan, 2022)
Education as a means of realizing quality human resources undergoes innovation in its management following the needs of the global community through thecurriculum set by the government. Currently, one of the focuses of education is to produce students who have soft-skills as the profile of Pancasila students. The purpose of this study was to improve the soft-skills profile of Pancasila students in class XI MIPA 4 SMAN 1 Muaro Jambi even in the 2021/2022 academic year through a virtual art exhibition project through classroom action research which was carried out using two cycles in February and March. in 2022. The results showed that the soft-skills profile of Pancasila students increased at the end of the cycle exceeding the expected performance indicators of 80%, reaching 90.31% for the mutual cooperation profile, and 89.10% for the creative profile.